Distinct gut microbiota and health outcomes in asymptomatic infection, viral nucleic acid test re‐positive, and convalescent COVID‐19 cases. Issue 2 (15th June 2022) - Lin, Ruqin; Xiao, Mingzhong; Cao, Shanshan; Sun, Yu; Zhao, Linhua; Mao, Xiaoxiao; Chen, Peng; Tong, Xiaolin; Ou, Zheyuan; Zhu, Hui; Men, Dong; Li, Xiaodong; et al.
Abstract: Gut microbiota composition is suggested to associate with coronavirus disease 2019 (COVID‐19) severity, but the impact of gut microbiota on health outcomes is largely unclear. We recruited 81 individuals from Wuhan, China, including 13 asymptomatic infection cases (Group A), 24 COVID‐19 convalescents with adverse outcomes (Group C), 31 severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) re‐positive cases (Group D), and 13 non‐COVID‐19 healthy controls (Group H). The microbial features of Groups A and D were similar and exhibited higher gut microbial diversity and more abundant short‐chain fatty acid (SCFA)‐producing species than Group C. Group C was enriched with opportunistic pathogens and virulence factors related to adhesion and toxin production. The abundance of SCFA‐producing species was negatively correlated, while Escherichia coli was positively correlated with adverse outcomes. All three groups (A, C, and D) were enriched with the mucus‐degrading species Akkermansia muciniphila, but decreased with Bacteroides ‐encoded carbohydrate‐active enzymes. The pathways of vitamin B6 metabolic and folate biosynthesis were decreased, while selenocompound metabolism was increased in the three groups. Specifically, the secondary bile acid (BA) metabolic pathway was enriched in Group A. Antibiotic resistance genes were common among the three groups. Conclusively, the gut microbiota was related to the health outcomes of COVID‐19. Dietary supplementations (SCFAs, BA, selenium, folate, vitamin B6) may be beneficial to COVID‐19 patients.